Bdellovibrio bacteriovorus directly attacks Pseudomonas aeruginosa and Staphylococcus aureus Cystic fibrosis isolates - Iebba, Valerio; Totino, Valentina; Santangelo, Floriana; Gagliardi, Antonella; Ciotoli, Luana; Virga, Alessandra; Ambrosi, Cecilia; Pompili, Monica; De Biase, Riccardo V.; Selan, Laura; Artini, Marco; Pantanella, Fabrizio; et al. (Frontiers in Microbiology, 2014)
Bdellovibrio bacteriovorus is a predator bacterial species found in the environment and within the human gut, able to attack Gram-negative prey. Cystic fibrosis (CF) is a genetic disease which usually presents lung colonization by Pseudomonas aeruginosa or Staphylococcus aureus biofilms. Here, we investigated the predatory behavior of B. bacteriovorus against these two pathogenic species with: (1) broth culture; (2) “static” biofilms; (3) field emission scanning electron microscope (FESEM); (4) “flow” biofilms; (5) zymographic technique. We had the first evidence of B. bacteriovorus survival with a Gram-positive prey, revealing a direct cell-to-cell contact with S. aureus and a new “epibiotic” foraging strategy imaged with FESEM. Mean attaching time of HD100 to S. aureus cells was 185 s, while “static” and “flow” S. aureus biofilms were reduced by 74 (at 24 h) and 46% (at 20 h), respectively. Furthermore, zymograms showed a differential bacteriolytic activity exerted by the B. bacteriovorus lysates on P. aeruginosa and S. aureus. The dual foraging system against Gram-negative (periplasmic) and Gram-positive (epibiotic) prey could suggest the use of B. bacteriovorus as a “living antibiotic” in CF, even if further studies are required to simulate its in vivo predatory behavior.